Fiscal Policy Independence in a European Monetary Union. (IMF Working Papers; Working Paper, 1990)
The issue of whether constraints should be placed on fiscal policies when moving to European monetary union is examined in the context of the use of fiscal policy for macroeconomic stabilization purposes. Examples of shocks hitting French and German economies are considered: an appreciation of their joint exchange rate against other currencies, an inflation shock, and an oil price increase. Except in the third case, flexible use of fiscal policies in the two countries is likely to give better outcomes than a system with constraints on their use. For the oil price shock, there seems to be a good case for policy coordination, not for ceilings on fiscal deficits.